Adult education responses to the 'othering' of Muslim identity: Perspectives from Ireland. Issue 2 (November 2017) - Fitzsimons, Camilla
This article explores the 'othering' of an erroneous fixed Muslim identity with an emphasis on its impacts within adult and community education. It examines the geopolitical circumstances that contribute to this othering and argues for the creation of counter-hegemonic, intercultural learning spaces.